Pengaruh Pendidikan Kesehatan Terhadap Peningkatan Pengetahuan Tentang Cerdas Bergaul dalam Mengenal Batasan dan Resiko Seks Bebas di SMA Negeri 1 Sunggal - Huwaina Af’idah; Nisrina Nisrina; Alfikri Syahtuah Siregar; Aura Naysilla; Abelia Putri; Izmi Raditya Putri (STIKES Columbia Asia Medan, 2025)
Adolescents are an age group that is vulnerable to various biological, psychological, and social changes. At this stage, adolescents face various challenges, including limitations in socializing and the risks of free sexual behavior, which can affect their physical, mental, and social health. Uncontrolled socializing and lack of understanding of the impacts of free sexual behavior often lead to reproductive health problems, such as unwanted pregnancies, sexually transmitted infections, and psychological stress. Therefore, an educational approach is needed that can guide adolescents to understand the limitations in socializing, manage emotions, and make wise decisions regarding interpersonal relationships. The purpose of this study was to increase adolescents' knowledge about Smart Socializing and Recognizing the Limits and Risks of Free Sex, so that they can understand and understand how to socialize intelligently and prevent themselves from the risks of free sex in their daily activities. This research method uses a quantitative design using pre-test and post-test questionnaires. The provision of pre-test and post-test questionnaires, according to the number of participants who took part in the socialization of smart socializing in recognizing the limits and risks of free sex. This study was conducted in December 2024 at SMA Negeri 1 Sunggal with a total of 80 respondents. The results of this socialization show that there is an increase in the knowledge of students of SMA Negeri 1 Sunggal by 56 (70%) after being given presentation materials by the PKM team. The conclusions and suggestions given are to improve Health Education, smart ways to socialize, knowing the Limits and prevention of free sex in adolescents.